Photonic Digitization With Differential Encoding Based on Orthogonal Vector Superposition - Shuna Yang; Hao Chi; Bo Yang; Ran Zeng; Jun Ou; Yanrong Zhai; Qiliang Li (IEEE Photonics Journal)
In this paper a novel photonic digitization scheme with differential encoding based on orthogonal vector superposition (OVS) is proposed and demonstrated. A phase modulator (PM) and two delay-line interferometers (DLIs) with π/2 difference in bias phase are employed to generate two orthogonal modulated signals. By adjusting and combining the intensity of two orthogonal signals with an OVS module, the desired phase shifts among different transfer functions can be obtained. The proposed scheme can differentially encode the input signal with enhanced bit resolution. Compared with the existing photonic digitization schemes based on modulators, this scheme features its simple configuration, because only a single PM, two DLIs and an OVS module are required; moreover, since the desired phase shifts of transfer functions are realized by attenuating the signal intensities, the proposed scheme can effectively alleviate the problem of phase bias drift induced by modulators. Proof-of-concept experiments of 3- and 4-bit photonic digitization systems based on OVS are successfully carried out, which demonstrate the feasibility of the approach.